The Influence of Life Orientation Sexuality Education on Attitudes to Sex and Sexuality in South Africa: A Systematic Review - Groth, Michelle (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
Youth in South Africa experience significant sexual and reproductive health problems, including high rates of STIs, HIV, unwanted pregnancy and sexual violence. Life Orientation (LO) sexuality education has been identified as crucial in promoting young people's well-being and equipping them to manage their sexual and reproductive lives in healthy ways. In this systematic review, a thematic analysis was conducted on 17 articles to identify and explore what themes were present in relation to the attitudes of educators in delivering sexuality education through LO and the influence of LO on youth attitudes to sex and sexuality. Of the 17 articles reviewed, six themes were identified and discussed. The findings highlight various shortcomings of LO in providing effective sexuality education and barriers that should be addressed to improve sexuality education in South Africa. To conclude, research that focuses on the attitudes of LO educators is important in order to identify areas in which they require increased support. In addition, research needs to continue to focus on the attitudes and experiences of youth through their own voices and perspectives in order to understand how sexuality education can meet their needs.
Keywords: Psychology -- South Africa; Sex instruction for youth -- South Africa; Sexual health -- South Africa; Sexually transmitted diseases -- Study and teaching -- South Africa; Sex educators -- South Africa -- Attitudes; Youth -- Sexual behavior -- South Africa; Youth -- Health and hygiene -- South Africa; Youth -- Counseling of -- South Africa; Youth -- Attitudes; Systematic review